2018
DOI: 10.15835/nsb10210238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seed Yield of Nigerian Bambara Groundnut [Vigna subterranea (L.) Verdc.] Landraces under Varying Water Conditions

Abstract: Seed yield of selected Nigerian Bambara Groundnut landraces under two varying water conditions was evaluated. Twenty eight (28) Bambara groundnut accessions were planted in a randomized complete block design with two treatments (Nonwater stressed and Water stressed) and replicated five times. The experiment was conducted at the Experimental Garden of the Department of Biological Sciences, Federal University of Technology, Minna, Niger State. The accessions were planted in planting bags during the cropping seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
1
10
1
Order By: Relevance
“…Furthermore, the correlations, which are positive between the yields obtained under stress-free growth conditions and negative between the yields obtained under stress conditions and the tolerance index, imply that a selection based on this index will lead to a drop in yield even in crop conditions without water stress. Similar results were reported by Farshadfar et al, (2012), Abejide et al, (2017), Abebe et al, (2020. Mean productivity, water stress tolerance index and yield index had significant positive correlations with yields under stress and non-stress conditions.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, the correlations, which are positive between the yields obtained under stress-free growth conditions and negative between the yields obtained under stress conditions and the tolerance index, imply that a selection based on this index will lead to a drop in yield even in crop conditions without water stress. Similar results were reported by Farshadfar et al, (2012), Abejide et al, (2017), Abebe et al, (2020. Mean productivity, water stress tolerance index and yield index had significant positive correlations with yields under stress and non-stress conditions.…”
Section: Resultssupporting
confidence: 90%
“…According to a survey, planting time has an effect on Bambara groundnut yield. Maximum yields were reported during the dry season, which had lower rainfall than the primary rainy season [52]. In comparison to forest climatic zones, the yield of Bambara groundnut is recorded as high in the alternation of agricultural climate with high temperature and low precipitation [36].…”
Section: General Production Scenario In Bambara Groundnutmentioning
confidence: 96%
“…The finding also reported that cultivating Bambara groundnut at the right time in the forest zone could give relatively higher yields. Another important attribute of Bambara groundnut is the availability of genotypes with varying maturity periods, ranging from 3 to 6 months, which makes it suitable for production and harvesting all year round, while minimizing yield loss [120].…”
Section: Research To Datementioning
confidence: 99%